Constitutive Activation of p62/Sequestosome-1-Mediated Proteaphagy Regulates Proteolysis and Impairs Cell Death in Bortezomib-Resistant Mantle Cell Lymphoma - Quinet, Grégoire (2022)
Funding Information: Funding: This work was supported at early stages by Spanish MINECO, CTQ2011–27874 grant. M.G.-S. is a fellow of the UbiCODE project funded by the EU’s Horizon 2020 research and innovation program under the Marie Skłodowska-Curie grant agreement No 765445.